Development of Interactive Multimedia-Based Physical Fitness Learning Media in Junior High School - Wiguno, Lokananta Teguh Hari; Kurniawan, Ari Wibowo; Wahyudi, Heri; Aqsha, Ahmad Hanif (Journal of Sport Science and Education, 2023)
This work seeks to provide a new teaching material for instructors in the physical fitness material of speed to aid teachers and students in the learning process and learning in physical education, sports, and health topics. This research and development method uses the Research and Development (R&D) approach developed by Lee & Owen. Small group trial subjects consisted of 20 students, large group trial subjects consisted of 30 students. Based on the results of product validation and trials, it was obtained 93% learning experts, 87% physical fitness experts, 91% media experts, 83% class VII user experts, 93% class VIII user experts, the results of the five validators met the criteria and were included in the category very valid and does not need to be revised. While small group trials for class VII were 83%, small group trials for class VIII were 82%, large group trials for class VII were 84%, large group trials for class VIII were 82%. From these results it was concluded that the development of this learning met the very good criteria and could be used to help the physical education learning process, especially on physical fitness material on the element of speed.